2022
DOI: 10.1111/nyas.14867
|View full text |Cite
|
Sign up to set email alerts
|

Memory modulations through musical pleasure

Abstract: Music, thanks to its strong evocative power, is considered a powerful mnemonic tool for both normal and clinical populations. However, the mechanisms underpinning the music‐driven benefits on memory remain unclear. In memory research, reward dopaminergic signals have been highlighted as a major modulator of memory traces consolidation. Over the last years, via behavioral and pharmacological approaches, we have investigated the hypothesis that dopaminergic‐dependent musical pleasure is a crucial mechanism under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…9B-C). While previous work has found that pleasure evoked by music can boost associative memory for non-musical information encoded during listening (in particular, through dopaminergic modulation of memory consolidation; see Ferreri & Rodriguez-Fornells, 2022), the present results indicate that such mood induction may not be sufficient to impact deliberate autobiographical recall. Alternatively, because hearing music may most strongly influence emotionally congruent memories (i.e., positively valenced music impacts positively valenced memories), it is possible that mismatch between music-evoked emotions and the emotional content of prompted memories diminished such effects (Sheldon et al, 2020;Talamini et al, 2022).…”
Section: Music-evoked Affect Was Not Sufficient To Impact Deliberate ...contrasting
confidence: 94%
“…9B-C). While previous work has found that pleasure evoked by music can boost associative memory for non-musical information encoded during listening (in particular, through dopaminergic modulation of memory consolidation; see Ferreri & Rodriguez-Fornells, 2022), the present results indicate that such mood induction may not be sufficient to impact deliberate autobiographical recall. Alternatively, because hearing music may most strongly influence emotionally congruent memories (i.e., positively valenced music impacts positively valenced memories), it is possible that mismatch between music-evoked emotions and the emotional content of prompted memories diminished such effects (Sheldon et al, 2020;Talamini et al, 2022).…”
Section: Music-evoked Affect Was Not Sufficient To Impact Deliberate ...contrasting
confidence: 94%
“…Meanwhile, listening to music often seems to lead to automatic and implicit learning of its structure ( Loui and Wessel, 2007 , 2008 ; Loui et al, 2010 ; Hansen and Pearce, 2014 ; Barascud et al, 2016 ). Better recollection of musical pieces, indicative of learning, is also associated with greater pleasure during listening – unless dopaminergic signaling is dampened (reviewed in Ferreri and Rodriguez-Fornells, 2022 ). These findings suggest that musical reward and pleasure may at least in part arise from gaining information about musical structure, i.e., sensory events (see, e.g., Vuust and Kringelbach, 2010 ; Zald and Zatorre, 2011 ; Gebauer et al, 2012 ; Koelsch et al, 2019 ; Vander Elst et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Music-driven emotional modulations can play a role in boosting cognitive, social and motor functions (Chanda et al, 2013;Ferreri et al, 2022;Fiveash et al, 2023;Fukui et al, 2014;Ripollés et al, 2016). A recent study found that listening to groovy (i.e., related to the pleasure and urge to move) music (featuring low to medium syncopation levels) boosted activity in the left DLPFC, and enhanced executive functions (i.e., response times in a Stroop task), in particular for participants who felt positively affected and groovy (Fukuie et al, 2022).…”
Section: Musical Affect and Its Implications In Cognitive Functionsmentioning
confidence: 99%